Analisis Faktor-faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Universitas Mataram dalam Pemilihan Profesi sebagai Akuntan Publik - Reny Wardiningsih (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Public accounting is one of the professions that assists the public in providing information for decision making, especially with regard to finance. The purpose of this study was to determine the factors that influence the interest of accounting students to choose the public accounting profession. The factors used in this study are intrinsic value, income perception, labor market considerations, the strengths and weaknesses of the public accounting profession. The approach used is a quantitative approach to the survey method. Sampling used a convenience sampling technique of 100 Accounting students at the University of Mataram to fill out a questionnaire. Data processing in this study used SPSS 26.00 by testing multiple linear regression. Hypothesis testing uses the F test, t test and R square test. The results obtained from the F test (5.102) with a significance level of 0.001 <0.05. This means that all the independent variables used in this study have an influence on the interest of Mataram University Accounting students in choosing a profession as a public accountant. The results of the t test concluded that H3 was accepted, while H1, H2, and H4 were rejected. The results of the R Square test show that the independent variables explain 14.2% of the dependent variable, while 85.8% are explained by other variables outside this research model.